Correlation of anthropometric indicators for identifying insulin sensitivity and resistance - Matos, Lívia Nascimento (2011)
CONTEXT AND OBJECTIVES: Early detection of reduced insulin sensitivity (IS) and insulin resistance (IR) is desirable. The aim here was to evaluate correlations of anthropometric indicators for identifying IR or IS and determine the cutoff points of the most effective indicators. DESIGN AND SETTING: Cross-sectional study in the city of São Paulo. METHODS: Sixty-one individuals with normal fasting plasma glucose (NFPG) and 43 overweight women were analyzed. Body mass index (BMI), waist circumference (WC), waist-to-hip ratio, waist-to-height ratio (WHtR), conicity index and the HOMA-IS and HOMA-IR indices were determined. The correlations between the anthropometric indices and IS and IR were determined. ROC analysis was used to determine the areas under the curve (AUC) and cutoff points. RESULTS: Among the NFPG individuals, BMI (r = -0.50; P = 0.002) and WHtR (r = -0.45; P = 0.007) showed correlations with HOMA-IS (homeostasis model assessment of insulin sensitivity). The ROC curve demonstrated statistical significance for BMI (AUC = 0.769; P = 0.005), WHtR (AUC = 0.764; P = 0.01) and WC (AUC = 0.702; P = 0.04), and the best cutoff points were 33.3 kg/m2 , 0.67 and 100 cm, respectively. Among the overweight women, the best correlation with HOMA-IR was demonstrated by WHtR (r = 0.37; P = 0.01), and the best cutoff point was 0.70 (AUC = 0.61; P = 0.25). CONCLUSION: The most promising indicators for showing IS among the NFPG individuals were BMI, WHtR and WC. Among the overweight women, WHtR demonstrated greater correlation with IR.